Comparison of Antioxidant Activity and Phytochemical Screening of Fresh and Dried Moringa oliefera L. Tea - Melania Priska; Natalia Peni; Yosephina Payu Wao (CHEMICA: Jurnal Teknik Kimia, 2023)
The world is being hit by a new variant of Covid-19, namely Omicron. The Omicron variant is easily dispersed from the previous variant. To prevent transmission of this variant, people need to increase their body's resistance by consuming foods and drinks rich in antioxidants. Moringa leaf tea can be an alternative drink rich in antioxidants to increase endurance and prevent the speed of transmission of the Omicron variant of Covid-19. This study analyzes the presence or absence of secondary metabolites and antioxidant activity in fresh and dry moringa tea. Secondary metabolite compounds were tested using phytochemical screening, which included testing for alkaloids, flavonoids, phenolics, saponins, tannins, steroids, terpenoids, and glycosides, while for antioxidant activity, the DPPH method was used. Based on the test results, the two types of tea did not have antioxidant activity because the IC50 value was more than 250 ppm, namely 868.72 ppm for fresh moringa tea and 2851.67 ppm for dry moringa tea. However, when compared between fresh and dry moringa tea, both have an IC50 value of 1:3 ratio, where the IC50 value of fresh moringa tea is three times lower than that of dried moringa tea. In addition, the results of the phytochemical screening of the two types of tea were positive for several secondary metabolites, namely flavonoids, alkaloids, and saponins.